Chloride Catalytic Determination as Potential Tool to Assess Metal Ion Bioavailability in Water - Mafalda G. Pereira; Justyna Paluch; Raquel B. R. Mesquita; António O. S. S. Rangel (Chemosensors)
This paper focuses on the development of an environmentally friendly sequential injection (SI) method for the determination of chloride in water samples from dynamic water systems. Chloride quantification is highly relevant, as it may affect metal ion bioavailability and potential toxicity to the environment. The approach was established based on the catalytic reaction of chloride ions in the colorimetric reaction between 3,3′,5,5′-tetramethylbenzidine (TMB) and hydrogen peroxide. Optimisation studies were performed regarding several parameters such as reaction pH, reagent volume and concentration, reaction time, and flow rates. As such, it was possible to obtain a wide dynamic range of 60 to 1000 mM, with a limit of detection and quantification of 17 and 58 mM, respectively, and a relative standard deviation of 7%. Validation was performed by analysing 13 water samples from dynamic water systems, namely seawater, estuarine water, and estuarine harbour water, with the SI method developed and by comparing the results obtained to potentiometric titration as the reference method. The relative error of these comparisons was not significant (<10%). Interference studies were also performed and showed no significant effect on the performance of the system (interference percentage < 10%), proving that a robust and sensitive system was developed.